Statistical Modeling of Medical and Public Health Data: Length of Stay of Patients Dying in Hospitals and Terrorism Violence in Southern Thailand - Watcharin, Komolmalai (Prince of Songkla University, 2012)
Thesis (Ph.D.(Research Methodology))--Prince of Songkla University, 2012